2008
DOI: 10.1109/ismvl.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

On Fixed Points and Cycles in the Reed Muller Domain

Abstract: This paper studies cycles that appear by repeatedly applying the RM transform to a p-valued function. It is shown that there are nontrivial fixed points, which correspond to eigenvectors of the transform and a simple method is proposed to determine the maximum period of n-place functions for a given p. The concept of spectral diversity is introduced, which may be applied to characterize pvalued functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This means that the RM spectrum or the RMF spectrum of an n-place p-valued functions is again an n-place pvalued function, not necessarily different from the original one. (It has been shown that both transforms have fixed points [8], [9]). Moreover, both the RM and the RMF transforms have a Kronecker product structure.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the RM spectrum or the RMF spectrum of an n-place p-valued functions is again an n-place pvalued function, not necessarily different from the original one. (It has been shown that both transforms have fixed points [8], [9]). Moreover, both the RM and the RMF transforms have a Kronecker product structure.…”
Section: Introductionmentioning
confidence: 99%
“…The eigenfunctions of the Reed-Muller transform of Boolean and multiple-valued functions were examined in [12] and [8], respectively. For the Reed-Muller-Fourier transform, the study of the eigenfunctions was initiated in [7], and the following conjecture was formulated about the number of fixed points (note that it agrees with the result of [12] for h = 2).…”
Section: Introductionmentioning
confidence: 99%